Le turc, une langue sans genre grammatical : la solution pour une langue plus égalitaire ? - Eléonore de Beaumont (Glad!)
Two strategies coexist today to try to make the French language more egalitarian in terms of gender: fighting against the predominance of the masculine in the language and therefore in our representations can be achieved either by multiplying gender marks or, on the contrary, by erasing them. In order to reflect on the latter strategy, I propose to analyse the functioning of a language without grammatical gender, Turkish, in order to show that a language without grammatical gender is not necessarily a neutral language.